Growth and pulp production of eucalyptus trees affected by ceratocystis wilt - Benso, Lucas Antonio [UNESP]; Rangel, Amábili Alves [UNESP]; Tiburcio, Rafael Augusto Soares; Neto, Marlon Michel Antonio Moreira; Sartori, Maria Márcia Pereira [UNESP]; Furtado, Edson Luiz [UNESP] (Wiley, 2024)
Ceratocystis wilt is one of the most harmful diseases affecting eucalyptus crops and is associated with species of the complex Ceratocystis fimbriata sensu lato. This pathology leads to the obstruction of the vascular system in infected trees, resulting in symptoms such as branch wilting and death. The wood affected by the pathogen exhibits discolouration and changes in its chemical composition, which can impact the pulping process. Therefore, the objective of this work is to investigate the impact of ceratocystis wilt on growth and the pulping process when sampling whole diseased trees. For this, healthy and diseased eucalyptus trees at the harvest age of 7 years were cut down, and their dendrometric variables (diameter at breast height, height and volume) and disease severity (basal discolouration area and volume of discoloured tissue) were measured. All tree trunks, classified into different severity classes, were sampled individually, peeled, chipped and subjected to Kraft cooking (Kappa number 18 ± 0.5). Diseased trees, under the evaluated condition, exhibited an average volume of 2.5% with discolouration and a reduction in the volumetric growth of 18.1%. The wood from diseased trees showed no significant differences in the Kraft cooking variables when compared to healthy trees. This result suggests that ceratocystis wilt reduces the volumetric growth of affected trees; however, due to the low proportion of symptomatic wood observed, the utilization of wood from diseased trees does not influence pulping and can be used in the pulp production process.
Keywords: cellulose; root infection; vascular wilt; wood discolouration; xylem colonization